Effects of miR-107 on Breast Cancer Cell Growth and Death via Regulation of the PTEN/AKT Signaling Pathway. (8th February 2023) - Pan, Hua; Peng, Hongwei; Dai, Yun; Han, Bin; Yang, Guangming; Jiang, Nian; Zhou, Ping
Abstract : Objective . Investigate the influence of miR-107 on breast cancer cell growth and death through the PTEN/AKT signaling pathway. Method . As study subjects, the human breast cancer cell line MCF-7 and the normal breast cell line Hs 578Bst were chosen, and MCF-7 cells were, respectively, transfected with control miRNA and miR-107 inhibitor. CCK-8, flow cytometry, scratch assay, and Transwell assay were used to analyze the proliferation, apoptosis, and invasion, and in order to identify the proteins associated with apoptosis in each of the three categories, we used western blot analysis. Bcl-2, cleaved caspase-3, and cleaved caspase-9 expression, as well as PTEN/AKT signaling pathway-associated protein expression, are correlated. Result . The expression of miR-107 in MCF-7 cells was significantly greater than that in Hs 578Bst cells, with a P < 0.05 difference; compared to the blank and miRNA control groups, the miR-107 inhibitor group had a P < 0.05 difference. P < 0.05 showed a decrease in proliferation (42.52) but no difference in proliferation between the blank and miRNA control groups (P > 0.05); the miR-107 inhibitor group had higher apoptosis (38.96) with P < 0.05 than the blank group (4.85) and the miRNA control group (5.89); there was no difference in apoptosis between the blank and miRNA groups (P > 0.05). There was no significant difference between the blank group and the miRNA control group with P > 0.05; compared with the blank group, the miR-107 inhibitor group had a lower expression of Bcl-2 protein (0.18), in addition to the degraded paradigms (0.73) and caspase-9 protein concentrations (0.79), respectively. Conclusion . The PTEN/AKT signaling pathway may be regulated by miR-107 to limit breast cancer cell growth and increase apoptosis, which suggests that miR-107 may be exploited as a tumor marker for therapeutic therapy.